Durable virological response and functional cure of chronic hepatitis D after long‐term peginterferon therapy. Issue 2 (28th May 2021) - Hercun, Julian; Kim, Grace E.; Da, Ben L.; Rotman, Yaron; Kleiner, David E.; Chang, Richard; Glenn, Jeffrey S.; Hoofnagle, Jay H.; Koh, Christopher; Heller, Theo
Summary: Background: Hepatitis delta virus (HDV) infection is the most aggressive form of chronic viral hepatitis. Response rates to therapy with 1‐ to 2‐year courses of pegylated interferon alpha (peginterferon) treatment are suboptimal. Aims: To evaluate the long‐term outcomes of patients with chronic hepatitis D after an extended course of peginterferon. Methods: Patients were followed after completion of trial NCT00023322 and classified based on virological response defined as loss of detectable serum HDV RNA at last follow‐up. During extended follow‐up, survival and liver‐related events were recorded. Results: All 12 patients who received more than 6 months of peginterferon in the original study were included in this analysis. The cohort was mostly white (83%) and male (92%) and ranged in age from 18 to 58 years (mean = 42.6). Most patients had advanced but compensated liver disease at baseline, a median HBV DNA level of 536 IU per mL and median HDV RNA level of 6.86 log10 genome equivalents per mL. The treatment duration averaged 6.1 years (range 0.8‐14.3) with a total follow‐up of 8.8 years (range 1.7‐17.6). At last follow‐up, seven (58%) patients had durable undetectable HDV RNA in serum, and four (33%) cleared HBsAg. Overall, one of seven (14%) responders died or had a liver‐related event vs four of five (80%) non‐responders. Conclusions: With further follow‐up, an extended course of peginterferon therapy was found to result in sustained clearance of HDV RNA and favourable clinical outcomes in more than half of patients and loss of HBsAg in a third. Abstract : Average peginterferon treatment duration 6 years. At last follow‐up, 58% with undetectable HDV RNA and 33% with HBsAg clearance. Reduced rate of death or liver‐related events in responders.